Strategi Pengembangan Warung Madura dalam Meningkatkan Pendapatan di Kecamatan Jombang - Prasetyo, Muhamad Andhika Budi; Muna, Naily El; Ashlihah, Ashlihah (ARZUSIN, 2026)
Although microenterprise development strategies have been widely studied, research that specifically discusses the development of Warung Madura in increasing income from the perspective of Islamic economics remains limited. This study aims to analyze the business development strategies of Warung Madura in Jombang Subdistrict and their role in increasing income. This study used a qualitative approach with a case study design, involving four Warung Madura owners selected through purposive sampling. Data were collected through interviews, observation, and documentation, then analyzed using the interactive model of Miles and Huberman. The results show that business development strategies were carried out through simple planning, endeavor, family deliberation, and business evaluation by maintaining product availability, extending operating hours, providing good service, and implementing simple financial recording. These strategies played a role in increasing income through rapid inventory turnover and the ability of Warung Madura to meet the daily needs of the community. The conclusion of the study affirms that product availability, reasonable prices, service quality, and family-based management are important factors in increasing business income ethically and sustainably. The implications of this study provide theoretical contributions to the development of Islamic economics literature, particularly in the study of microenterprises based on family values and business ethics, as well as practical implications for Warung Madura owners in strengthening business management strategies. This study also opens opportunities for further research on financial management, business legality, and digital adaptation of Warung Madura.